Study of The Gastropoda Community in Cermin Coast, Paya Dua Village, Peudawa District, East Aceh District, Aceh - Ella Fizh Sahrin; Sri Jayanthi; Silvia Wardania; Sahna Maulana Sitakar; Muliani Tiana Sari; Rauzatul Jannah (Jurnal Biologi Tropis, 2023)
Cermin Beach is one of the beaches that has an abundant level of diversity and abundance of biota, one of which is the level of diversity of gastropods which have many roles as key organizations in food networks in waters. Gastropods as organisms that live in waters are very sensitive to changes in the water quality where they live. This research was conducted on November 25 2023 with the aim of knowing the types of Gastropods found at Cermin Beach, Paya Dua Village, Peudawa District and to determine the structure of the Gastropod community related to individual density, relative abundance, frequency of presence, diversity, evenness, and similarity of species by applying a survey method with primary data collection carried out using the Line Transet method, namely by walking along the intertidal zone along the specified transect line. The results show that at Cermin Beach in Paya Dua Village, Peudawa District, 46 species of gastropods were found with different numbers at each station. The relationship between physical and chemical factors in Cermin Beach waters also influences the diversity of Gastopoda.